Cinnamomum Species: Bridging Phytochemistry Knowledge, Pharmacological Properties and Toxicological Safety for Health Benefits - Sharifi-Rad, Javad; Dey, Abhijit; Koirala, Niranjan; Shaheen, Shabnum; El Omari, Nasreddine; Salehi, Bahare; Goloshvili, Tamar; Cirone Silva, Nathália Cristina; Bouyahya, Abdelhakim; Vitalini, Sara; Varoni, Elena M.; Martorell, Miquel; et al. (Frontiers in Pharmacology, 2021)
The genus Cinnamomum includes a number of plant species largely used as food, food additives and spices for a long time. Different traditional healing systems have used these plants as herbal remedies to cure diverse ailments. The aim of this comprehensive and updated review is to summarize the biodiversity of the genus Cinnamomum, its bioactive compounds, the mechanisms that underlie the pharmacological activities and toxicological safety. All the data in this review have been collected from databases and recent scientific literature including Web of Science, PubMed, ScienceDirect etc. The results showed that the bioactive compounds of Cinnamomum species possess antimicrobial, antidiabetic, antioxidant, anti-inflammatory, anticancer and neuroprotective effects. The preclinical (in vitro/in vivo) studies provided the possible molecular mechanisms of these action. As a novelty, recent clinical studies described in this paper support and confirm the pharmacological importance of the genus Cinnamomum. In conclusion, the obtained results from preclinical studies and clinical trials, as well as reduced side effects provide insights into future research of new drugs based on extracts and bioactive compounds from Cinnamomum plants.